Answer: (2*p + 3)/q
Step-by-step explanation:
First, let's remember the relationships:
Logₙ(a) = Ln(a)/Ln(n)
Ln(A*B) = Ln(A) + Ln(B)
Ln(a^n) = n*Ln(a)
Now, we know that:
Logₓ(2) = p
Logₓ(7) = q
We want to express:
Log₇(4*x^3) in terms of p and q.
First, we can rewrite the first two relations as:
Ln(2)/Ln(x) = p
Ln(7)/ln(x) = q
then we have:
Ln(2) = p*Ln(x)
Ln(7) = q*Ln(x)
Ok:
Now let's play with our equation:
Log₇(4*x^3)
First, this is equal to:
Ln(4*x^3)/Ln(7)
We now can rewrite this as:
(Ln(4) + Ln(x^3))/Ln(7)
= (Ln(2^2) + Ln(x^3))/Ln(7)
= (2*Ln(2) + 3*Ln(x))/Ln(7)
Now we can replace Ln(2) by p*Ln(x) and Ln(7) by q*Ln(x)
(2*p*Ln(x) + 3*Ln(x))/(q*Ln(x)) = (2*p + 3)/q
This is the expression we wanted.
<h3>
Answer: Reflect over the y axis</h3>
=====================================================
Explanation:
We have these two given functions
The change is that the x has been replaced with -x
We can say
f(x) = x+7
f(-x) = -x+7 ... replace each x with -x
g(x) = f(-x)
g(x) = -x+7
When we replace x with -x, we're flipping the x inputs from positive to negative, and vice versa. This visually will reflect the line over the vertical y axis. A point like (1,8) on f(x) reflects over to (-1,8) on g(x).
As another example, the point (-5,2) on f(x) reflects over the y axis to arrive at (5,2) on the g(x) function.
Here is your answer. If you need an explanation, let me know.
Answer:
A. 2.2402
Step-by-step explanation:
The sides
12-3a
12-3a
4(2a-5)=8a-40
so for perimeter we + them
(12-3a)+(12-3a)+(8a-40)
=
2a-16